The Effect Of Fasting On The Growth Response Of Chopped Grouper Fish (Epinephelus fuscoguttatus x Epinephelus lanceolatus) - Indriana Citra Dewi; Wiwin Kusuma Atmaja Putra; Tri Yulianto (ECOTONE, 2020)
This research aims to determine the effect of appropriate feeding time for the growth of Chopped Grouper Fish (Epinephelus fuscoguttatus x Epinephelus lanceolatus). This research was conducted from March to April 2020 for 42 days at Madong village, silver pompano culture group, Tanjungpinang City, Riau Islands Province. The methodology used in this research was experimental with a completely randomized design (CRD) with 3 treatments and 4 replications, which the T1: fed daily  T2: 1 day given food 1 day of fasting. T3: 2 days given food, 1 day of fasting. Analysis of the data using One-Way ANOVA showed that the best absolute weight growth was found in T1 treatment of (29.13 ± 1.07 g), daily growth (SGR) (0.69 ± 0.03 cm). The results obtained indicate that T1 treatment is the best treatment for growth